Malićević, S. (2024). Sports Medicine - Selected Chapters (Sport - nauka i praksa, 2025)
The book “Sports Medicine – Selected Chapters” by Prof. Sead Malićević, PhD is a comprehensive guide covering various aspects of the broad domain of sports medicine. Through six thematic sections, it thoroughly examines key topics essential for athletes, coaches, and medical professionals engaged in safeguarding and improving athletes' health.